MODERN CLINICAL AND LABORATORY APPROACHES TO THE DIAGNOSIS OF PNEUMONIA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Pneumonia is one of the most common and clinically significant diseases of the respiratory system, associated with high morbidity and a substantial risk of complications. Timely and accurate diagnosis of pneumonia is crucial for selecting appropriate treatment strategies and improving disease outcomes. In recent years, modern laboratory diagnostic methods have been widely implemented in clinical practice, enabling the detection of inflammatory processes, identification of the etiological agent, and assessment of disease severity. This paper reviews current approaches to the clinical and laboratory diagnosis of pneumonia, including general clinical, biochemical, immunological, and molecular genetic methods. Special attention is paid to the role of inflammatory laboratory markers, such as C-reactive protein, procalcitonin, complete blood count parameters, and microbiological studies, in the diagnosis of pneumonia and in monitoring the effectiveness of therapy.